2013
DOI: 10.1177/0192513x13497349
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, Validity, and Associations With Sexual Behavior Among Ghanaian Teenagers of Scales Measuring Four Dimensions of Relationships With Parents and Other Adults

Abstract: Little research has been done on the social contexts of adolescent sexual behaviors in sub-Saharan Africa. As part of a longitudinal cohort study (N=1275) of teenage girls and boys in two Ghanaian towns, interviewers administered a 26 item questionnaire module intended to assess four dimensions of youth-adult relationships: monitoring conflict, emotional support, and financial support. Confirmatory factor and traditional psychometric analyses showed the four scales to be reliable. Known-groups comparisons prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Seven items from the Inventory of Parent and Peer Attachment (Armsden and Greenberg 1987) and the Network of Relationships Inventory (Furman and Buhrmester 2009) were adapted to measure family support in a manner reflecting the importance of extended family kin in Ghana (Bingenheimer et al 2015). Each item begins with the phrase, “There is an adult in your life who…”, and end with: “comforts you”, “gives you advice”, “praises you”, “gives you attention”, “encourages you”, “trusts you”, and “understands you”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven items from the Inventory of Parent and Peer Attachment (Armsden and Greenberg 1987) and the Network of Relationships Inventory (Furman and Buhrmester 2009) were adapted to measure family support in a manner reflecting the importance of extended family kin in Ghana (Bingenheimer et al 2015). Each item begins with the phrase, “There is an adult in your life who…”, and end with: “comforts you”, “gives you advice”, “praises you”, “gives you attention”, “encourages you”, “trusts you”, and “understands you”.…”
Section: Methodsmentioning
confidence: 99%
“…Greater parental monitoring and closer, more nurturing parent–youth relationships are associated with less self-reported sexual risk behavior among youth in Ghana and other sub-Saharan African countries (Biddlecom et al 2009; Bingenheimer et al 2015). As adolescent sexual risk often co-occurs with adolescent mental health, it is reasonable to consider how family processes may influence changes in depressive symptoms over the course of adolescence for youth in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…their education and income) are linked to adolescents’ sexuality [ 38 ]. In the literature, parents with high levels of education and/or income are seen to offer closeness, warmth, monitoring and protection [ 38 , 39 ]. This has been linked to less sexual activity among adolescents and accordingly suggests less “assertive” and “agentic” sexual self-views.…”
Section: Introductionmentioning
confidence: 99%
“…They were developed from preexisting instruments, 7275 and their psychometric properties have been described elsewhere. 51 The behavioral control scale consists of six items (e.g., “There is an adult in your life who knows where you are at night”) and has a Cronbach's alpha of 0.73. The relationship quality scale consists of nine items (e.g., “There is an adult in your life who listens to you”) and has a Cronbach's alpha of 0.80.…”
Section: Methodsmentioning
confidence: 99%
“…50,51 Conversely, several U.S. studies 46,52,53 have shown that conflict with parents is associated with sexual activity and involvement in romantic relationships. These associations may reflect processes in which females who have lower-quality relationships with their parents or family adults, and who experience more conflict with these individuals, are more likely to form romantic and sexual relationships with young men as a means of getting emotional support and validation that they do not receive from their families.…”
mentioning
confidence: 99%